GURU BAHASA SEBAGAI CERMIN DALAM PEMBENTUKAN KARAKTER KRITIS DAN KREATIF SISWA: Pembentukan Karakter Kritik dan Kreatif - Anam Besari (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2020)
Recently, it takes people who have critical and creative character. Both characters can be develop through a process of education, including through language subjects. The critical and creative character of students can develop or be developed with a process of habituation, either through learning or exemplary they get naturally through what students see in their teachers. Likewise people learn language, what is gained through acquisition will make a lasting impression than what is gained through learning. The process of learning to read and write can be used as a means of developing student’s critical and creative thinking. Reading can be much help in developing critical thinking skills, and learning to write can be much help develop creative thinking abilities. However in teaching of writing, teachers should be exemplary in terms of writing, in the end, students writing creativity will develop faster. Therefore, it is not enough for the language teacher to convey the theory well, but also must be able to be a model as well as an example in producing good writing.